Age-period-cohort analysis of hepatitis A incidence rates in Korea from 2002 to 2012 - Seo, Joo Yeon (Epidemiol Health, 2016)
OBJECTIVES: This study aimed to evaluate the epidemiology of hepatitis A in Korea from 2002 to 2012 using age-period-cohort analyses. METHODS: We used claims data from the Korean National Health Insurance Corporation for the entire population. Census data from 2010 were used as the standard population. The incidence of hepatitis A was assumed to have a Poisson distribution, and the models and effects were evaluated using the intrinsic estimator method, the likelihood ratio, and the Akaike information criterion. RESULTS: The incidence of hepatitis A gradually increased until 2007 (from 17.55 to 35.72 per 100,000 population) and peaked in 2009 (177.47 per 100,000 population). The highest incidence was observed among 27-29-year-old individuals when we omitted data from 2005 to 2007. From 2005 to 2007, the peak incidence was observed among 24-26-year-old individuals, followed by 27-29-year-olds. The best model fits were observed when the age-period-cohort variables were all considered at the same time for males, females, and the whole population. CONCLUSIONS: The incidence of hepatitis A exhibited significant age-period-cohort effects; its incidence peaked in 2009 and was especially high among Koreans 20-39 years of age. These epidemiological patterns may help predict when high incidence rates of hepatitis A may occur in developing countries during their socioeconomic development.